Setting Up the Perimeter of Tolerance: Insights into mTEC Physiology - Rodrigues, PM (2018)
Medullary thymic epithelial cells (mTECs) play a central role in T cell tolerance. However, how the mTEC compartment is maintained remains elusive. We review recent discoveries on new transcription factors involved in mTEC homeostasis and discuss the poss